2018
DOI: 10.1016/j.virol.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for contemporary plant mitoviruses

Abstract: Mitoviruses have small RNA(+) genomes, replicate in mitochondria, and have been shown to infect only fungi to date. For this report, sequences that appear to represent nearly complete plant mitovirus genomes were recovered from publicly available transcriptome data. Twenty of the refined sequences, 2684-2898 nt long and derived from 10 different species of land plants, appear to encompass the complete coding regions of contemporary plant mitoviruses, which furthermore constitute a monophyletic cluster within g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(107 citation statements)
references
References 66 publications
3
94
0
Order By: Relevance
“…Viruses belonging to Narnaviridae are divided into Narnavirus and Mitovirus genera, which are thought to differ for the site of replication: viruses belonging to Narnavirus genus replicate in cytosol whereas the majority of viruses belonging to Mitovirus genus replicate in mitochondria (Hillman and Cai, ). Viruses belonging to the latter genus were believed to be hosted only by fungi, but recent reports demonstrated that they are widespread also in plants (Nibert et al ., ). In the present work, we identified five viruses belonging to Mitovirus and four viruses belonging to Narnavirus genus.…”
Section: Resultsmentioning
confidence: 97%
“…Viruses belonging to Narnaviridae are divided into Narnavirus and Mitovirus genera, which are thought to differ for the site of replication: viruses belonging to Narnavirus genus replicate in cytosol whereas the majority of viruses belonging to Mitovirus genus replicate in mitochondria (Hillman and Cai, ). Viruses belonging to the latter genus were believed to be hosted only by fungi, but recent reports demonstrated that they are widespread also in plants (Nibert et al ., ). In the present work, we identified five viruses belonging to Mitovirus and four viruses belonging to Narnavirus genus.…”
Section: Resultsmentioning
confidence: 97%
“…2B) and replicate in mitochondria and in the cytosol of the host cells of fungal and invertebrate hosts, respectively (the latter hosts were identified in metaviromic holobiont analyses) (14,53). Recently, the existence of plant "mitoviruses" has been reported although it is not known whether these viruses reproduce in the mitochondria (54). The "narnavirus" RdRp is also the ancestor of the RdRp of the expanding group of "ourmiaviruses" ( Fig.…”
Section: Evolution Of the 5 Major Branches Of Rna Viruses And Reconstmentioning
confidence: 99%
“…In addition, all of the integrated plant mitochondrial sequences are very similar, and hence are likely monophyletic (Bruenn et al ., ). The congruence between the phylogenies of the recently described putative plant mitoviruses and those of the plant hosts implies an ancient origin, but it does not shed light on the ultimate origin of mitoviruses or transmission among plants and fungi (Nibert et al ., ).…”
Section: Lineages Shared By Plant and Fungal Virusesmentioning
confidence: 97%
“…Analyses of these transcripts support the idea that they are indeed mitoviruses of plants, rather than sequences integrated into the plant mitochondrial genomes. They were found in a wide range of plants, some of which diverged > 30 Ma (Nibert et al, 2018).…”
Section: The Mitovirusesmentioning
confidence: 99%
See 1 more Smart Citation